1995
DOI: 10.1002/1097-4679(199509)51:5<703::aid-jclp2270510516>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Burnout and collegial support in state psychiatric hospital staff

Abstract: To determine the correlates of burnout, 47 employees of a state psychiatric hospital completed measures of burnout, collegia! support, prolonged anxiety, physical health, and job attitude. Results showed that burnout was associated positively with anxiety, frequency of illness, and contrary job attitudes, and correlated negatively with level of satisfaction with the collegial support network. Partial correlations showed that satisfaction with support systems diminished the effects of burnout on frequency of il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 11 publications
4
40
0
5
Order By: Relevance
“…For example, Reid et al (1999a, b) found that specific coping strategies such as informal contacts with colleagues promoted job satisfaction, in turn lowering burnout. This buttressed the prior work that describes a meaningful association between collegial support and burnout (Corrigan, Holmes, & Luchins, 1995). However, as no interventions have yet shown to be effective in reducing burnout and secondary trauma, suggestions to this end cannot be offered.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Reid et al (1999a, b) found that specific coping strategies such as informal contacts with colleagues promoted job satisfaction, in turn lowering burnout. This buttressed the prior work that describes a meaningful association between collegial support and burnout (Corrigan, Holmes, & Luchins, 1995). However, as no interventions have yet shown to be effective in reducing burnout and secondary trauma, suggestions to this end cannot be offered.…”
Section: Discussionmentioning
confidence: 99%
“…A sampling of these strategies, which have been described at various levels of detail, includes the following: (1) competitive salaries, (2) financial and non-financial incentives to enhance staff motivation and morale, (3) opportunities for promotion and career advancement, (4) funding for increased staffing levels, (5) training staff on self-care strategies, (6) additional clinical supervision and mentoring, (7) clear job descriptions/expectations, (8) routine assessment of burnout, (9) flexible work schedules, (10) social events and informal support, (11) in service trainings, and (12) open-door policies with management. 7,9,32,[35][36][37][38][39] All of the above cited actions may have a potential impact in decreasing the negative consequences associated with burnout and its effect on turnover, but as previously stated, the empirical support for these interventions is lacking.…”
Section: Interventions To Decrease Burnoutmentioning
confidence: 99%
“…For example, a perceived lack of collegial supports has been associated with burnout among psychiatric workers (Corrigan, Holmes, & Luchins, 1995;Corrigan et al, 1994). K. I.…”
Section: Evidence For the Importance Of Relatednessmentioning
confidence: 99%